To write the equation of a line in point-slope form, you can use the formula:
\[ y - y_1 = m(x - x_1) \]
where \(m\) is the slope, and \((x_1, y_1)\) is a point on the line.
Given the point \((-2, 6)\) and the slope \(m = -4\), you can substitute these values into the formula:
- \(x_1 = -2\)
- \(y_1 = 6\)
- \(m = -4\)
Now plug these values into the point-slope form:
\[ y - 6 = -4(x - (-2)) \]
This simplifies to:
\[ y - 6 = -4(x + 2) \]
You can rewrite the equation in point-slope form as:
\[ y - 6 = -4(x + 2) \]
So, the final answer is:
\[ y - 6 = -4(x + 2) \]